Unzureichender Therapieerfolg nach metabolisch-bariatrischer Operation: medikamentös additive Therapie oder chirurgische Konversion? : Leitthema - Lauerer, Jakob Franz; Kollmann, Lars; Koschker, Ann-Cathrin; Otto, Mirko; Seyfried, Florian Johannes David (Die Chirurgie, 2025)
Morbid obesity is a recognized chronic disease. Metabolic bariatric surgery (MBS) currently represents the most effective treatment, with efficacy in achieving significant weight reduction and improving obesity-related comorbidities, quality of life and overall survival; however, unsatisfactory treatment outcomes manifesting as suboptimal weight loss, recurrent weight gain, or poor control of comorbid conditions, represent a clinically relevant challenge requiring further treatment. Conversion surgery can positively influence weight trajectories and associated comorbidities but are associated with higher risk profiles compared to primary procedures. Additive pharmacological treatment, particularly glucagon-like peptide 1 (GLP-1) analogues, also demonstrate efficacy with an acceptable side effect profile. This article examines the definitions of suboptimal treatment success following MBS and provides an overview of available treatment options as well as the decision-making process for individualized treatment. Special attention must be paid to the comorbidities and the preferences of patients within an interdisciplinary framework supported by appropriate clinical expertise.
Gesehen am 21.10.2025